Improvement After Vestibular Rehabilitation Not Explained by Improved Passive VOR Gain - Millar, Jennifer L.; Gimmon, Yoav; Roberts, Dale; Schubert, Michael C. (Frontiers in Neurology, 2020)
Gaze stability exercises are a critical component of vestibular rehabilitation for individuals with vestibular hypofunction and many studies reveal the rehabilitation improves functional performance. However, few studies have examined the vestibular physiologic mechanisms (semicircular canal; otolith) responsible for such recovery after patients with vestibular hypofunction complete gaze and gait stability exercises. The purpose of this study was to compare behavioral outcome measures (i.e. visual acuity during head rotation) with physiological measures (i.e. gain of the vestibulo-ocular reflex) of gaze stability following a progressive vestibular rehabilitation program in patients following unilateral vestibular deafferentation surgery. We recruited n = 43 patients (n=18 female, mean 52 ±13 years, range 23 – 80 years) after unilateral deafferentation from vestibular schwannoma; n=38 (25 female, mean 46.9 ± 15.9 years, range 22-77 years) age-matched healthy controls for dynamic visual acuity testing, and another n= 28 (14 female, age 45±17, range 20-77 years) healthy controls for video head impulse testing. Data presented is from n=19 patients (14 female, mean 48.9 ± 14.7 years) with UVD who completed a baseline assessment approximately 6 weeks after surgery, five-weeks of vestibular physical therapy and a final measurement. As a group, subjective and fall risk measures improved with a meaningful clinical relevance. Dynamic visual acuity (DVA) during active head rotation improved (mean ipsilesional 38.57% ± 26.32 (n=15/19); mean contralesional 39.96% ± 22.62 (n=12/19), though not uniformly. However, as a group passive yaw VOR gain (mean ipsilesional pre 0.44 ± 0.18 vs post 0.44 ± 0.15; mean contralesional pre 0.81 ± 0.19 vs post 0.85 ± 0.09) did not show any change (p ≥ 0.4) after rehabilitation. The velocity of the overt compensatory saccades during ipsilesional head impulses were reduced after rehabilitation;no other metric of oculomotor function changed (p ≥ 0.4). Preserved utricular function was correlated with improved yaw DVA and preserved saccular function was correlated with improved pitch DVA. Our results suggest that five weeks of vestibular rehabilitation using gaze and gait stability exercises improves both subjective and behavioral performance despite absent change in VOR gain in a majority of patients, and that residual otolith function appears correlated with such change.